2011
DOI: 10.1038/ki.2010.385
|View full text |Cite
|
Sign up to set email alerts
|

Dicer regulates the development of nephrogenic and ureteric compartments in the mammalian kidney

Abstract: MicroRNAs (miRNAs) are a large and growing class of small, non-coding, regulatory RNAs that control gene expression predominantly at the post-transcriptional level. The production of most functional miRNAs depends on the enzymatic activity of Dicer, an RNase III class enzyme. To address the potential action of Dicer-dependent miRNAs in mammalian kidney development, we conditionally ablated Dicer function within cells of nephron lineage and the ureteric bud-derived collecting duct system. Six2Cre-mediated remov… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

5
140
0

Year Published

2012
2012
2018
2018

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 153 publications
(146 citation statements)
references
References 61 publications
5
140
0
Order By: Relevance
“…In this study, mice lacking Dicer in kidney tubules and collecting ducts exhibit hydronephrosis, hydroureter, and cyst formation. 8 Although a similar phenotype was reported previously, 6,7 Patel et al further extend their analysis to mechanistically explain the phenotype. 8 Small RNA profiling identified multiple miRNAs downregulated in Dicer mutant kidneys.…”
mentioning
confidence: 54%
See 1 more Smart Citation
“…In this study, mice lacking Dicer in kidney tubules and collecting ducts exhibit hydronephrosis, hydroureter, and cyst formation. 8 Although a similar phenotype was reported previously, 6,7 Patel et al further extend their analysis to mechanistically explain the phenotype. 8 Small RNA profiling identified multiple miRNAs downregulated in Dicer mutant kidneys.…”
mentioning
confidence: 54%
“…2 Thus, it is very surprising that in one of the most abundant human diseases, polycystic kidney disease (PKD), miRNAs have thus far only been implicated intermittently and direct mechanistic data are scarce. [3][4][5][6][7] The article by Patel et al in this issue of JASN now demonstrates a direct link between cyst formation, miRNAs, and Polycystin-1, the gene most frequently mutated in human autosomal dominant PKD (ADPKD). 8 Patel et al used one of the most fruitful approaches to explore the role of miRNAs in organogenesis-the conditional ablation of Dicer, a key enzyme in miRNA biogenesis.…”
mentioning
confidence: 99%
“…At the end of these experimental models different phenotypes have emerged. Based on these different results it was reported that miRNAs played role not only in kidney development and maintaining normal kidney functions but also in the pathogenesis of kidney disease [23][24][25][26][27][28][29][30][31] . As a limitation of our study, due to small sample size our results might not reflect the actual relation between DICER gene frequency and CAKUT.…”
Section: Discussionmentioning
confidence: 99%
“…They exert their function by binding to the 3'-untranslated region of their target mRNAs and thus either induce mRNA degradation (Guo et al 2010;Hendrickson et al 2009) or inhibit translation (Mathonnet et al 2007;Thermann and Hentze 2007). Results from mice carrying conditional null mutations for dicer, an enzyme required for the cleavage of pre-miRs into mature miRs (Bernstein et al 2001), indicate the essential role of miRNAs in many cellular processes (Cuellar et al 2008;Davis et al 2011;Harris et al 2006;Harfe et al 2005;Nagalakshmi et al 2011). MicroRNAs are believed to contribute to the specification and differentiation of various cell types including neurons (Åkerblom et al 2012;Yu et al 2008;Stappert et al 2013).…”
Section: Introductionmentioning
confidence: 99%